Periplasmic expression of EGFRvIII extracellular domain as a fusion protein in Escherichia coli NiCo21(DE3). Issue 1 (May 2021) - Dewi, K S; Aminah,; Fuad, A M
Abstract: Epidermal growth factor receptor variant III is a mutant variant of EGFR that has a deletion on its DNA encoding extracellular ligan-binding domain. EGFRvIII is only found in cancer cells and not in normal cells, make it an ideal target as a biomarker for antibody-based cancer therapy. This study performed the expression and characterization of EGFRvIII extracellular domain conjugated with a blue fluorescent protein (BFP) as a fusion protein in Escherichia coli periplasmic space. Endoxylanase signal peptide was employed to guide the recombinant protein through the membrane. IPTG as inducer was added into expression medium with various concentrations of 0; 0.1; 0.25; 0.5; 1 mM, followed by periplasmic extraction using the hypertonic solution. Total proteins and periplasmic proteins were characterized using SDS-PAGE and slot blot analyses. Extracellular domain of EGFRvIII-BFP fusion protein was detected using confocal fluorescence microscopy. This study showed that the ∼43 kDa target protein was successfully expressed on E. coli NiCo21(DE3) periplasmic space with optimum IPTG concentration of 0.1 mM and and showed a blue fluorescence color under the microscope..